Producing Migrant Domestic Work: Exploring the Everyday Political Economy of Malaysia's 'Maid Shortage'. Issue 6 (1st November 2016) - Elias, Juanita; Louth, Jonathon
Abstract: The article considers how the employment of domestic workers by middle-class Malaysian households has been thrown into flux by the imposition of bans on the sending of workers by states such as Indonesia and Cambodia, as well as the decline in numbers of women seeking employment as domestic workers in Malaysia and rising employment costs. This article does not seek to focus on the high-level policy negotiations and disputes that have come to characterize systems of temporary return migration for domestic work in Asia, but to focus in on the everyday political economies (of social reproduction, work, and everyday agency) that constitute the conditions of possibility within which bilateral disputes and labour agreements between Southeast Asian states take shape. We examine three dimensions of migration for domestic work in Southeast Asia in ways that bring together literatures on everyday life and social reproduction. These interconnected yet distinct dimensions are (a) the relationship between strategies to boost remittances and flows of workers from some of the most impoverished parts of Southeast Asia; (b) the centrality of low-cost migrant domestic workers to Malaysian middle-class 'success stories', and (c) the day-to-day production of 'good' worker subjects—a process that is actively and constantly resisted by workers themselves. The article provides important insights into the mechanisms through arenas of everyday life—and the household in particular—are transformed; becoming sites for the ever widening and deepening of the market economy.